Preparation method of polyacrylic acid-based powder wound dressing

The polyacrylic acid-based powder dressing prepared by copolymerizing THMA and AA solves the problems of poor adhesion and insufficient anti-inflammatory properties of polyacrylic acid-based dressings under moist conditions, achieving efficient wet adhesion and anti-inflammatory effects, and is suitable for diverse wound care.

CN119258262APending Publication Date: 2025-01-07HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411257040.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing polyacrylic acid-based wound dressings have poor adhesion under moist conditions and insufficient anti-inflammatory and drug-loading properties, failing to meet diverse clinical needs.

Method used

By copolymerizing N-[tris(hydroxymethyl)methyl]acrylamide (THMA) with acrylic acid (AA) to form P(AA-co-THMA) powder, and then mixing it with drugs, a polyacrylic acid-based powder dressing is prepared. The trihydroxy structure of THMA enhances hydrogen bonding and non-covalent interactions, thereby improving adhesion and drug loading capacity.

Benefits of technology

The prepared polyacrylic acid-based powder dressing exhibits good adhesion and anti-inflammatory properties in a wet state, is easy to store, adapts to irregularly shaped wounds, and promotes wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258262A_ABST
    Figure CN119258262A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a polyacrylic acid-based powder wound dressing, which comprises the following steps: copolymerizing N-[tris (hydroxymethyl) methyl] acrylamide and an acrylic acid solution by adopting photopolymerization, dialyzing, pre-freezing, freeze-drying and grinding to obtain AA-co-THMA powder; the preparation method comprises the following steps: respectively dissolving AA-co-THMA powder and a medicine in deionized water to respectively obtain an AA-co-THMA solution and a medicine solution, mixing the AA-co-THMA solution and the medicine solution into gel, and pre-freezing, freeze-drying and grinding to obtain the polyacrylic acid-based powder dressing. N-[tris (hydroxymethyl) methyl] acrylamide (THMA) and acrylic acid are copolymerized, a THMA trihydroxy structure can shield a repulsive effect between acrylic acid carboxyl groups, hydrogen bonds can be generated between THMA trihydroxy structure and acrylic acid carboxyl groups, and hydrogen bonds can also be formed between THMA, so that a more stable gel cross-linked network can be formed; meanwhile, trihydroxy of THMA can also form a non-covalent effect with polyhydroxy drugs, so that the drug loading capacity is improved, and the very good wet tissue adhesion performance of THMA can also be exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a method for preparing a wound dressing, in particular to a method for preparing a polyacrylic acid-based powder wound dressing, and belongs to the field of wound dressing preparation in biomedical materials. Background Art

[0002] As the first natural barrier of the human body, the skin plays an important role in protecting the internal tissues and organs from damage, blocking the invasion of microorganisms, and maintaining the stability of the internal environment. When the skin is severely damaged by surgery, burns, skin diseases, etc., it loses its protective function and may also cause a series of complex health problems, including inflammation, secondary damage, bacterial infection, etc.

[0003] Hydrogel wound dressings are widely used in skin wound repair due to their good hydrophilicity, biocompatibility and extracellular matrix-like three-dimensional porous structure (Zhao Y., Chem. Rev. 2022, 122, 5604-5640; Matoori S., Sci. Transl. Med. 2021, 13, eabe4839). Compared with traditional dry dressings such as gauze and medical cotton, hydrogel dressings can provide a moist healing environment for the wound, which is conducive to tissue regeneration and cell migration at the wound, while reducing the secondary damage that may be caused during the dressing change process. However, with the aging of the world's population, the care of chronic wounds such as bedsores and ulcers that are closely related to the elderly is gradually becoming an increasingly serious health problem. Ordinary hydrogel dressings with a single structure and function can no longer meet diverse clinical needs. Therefore, it is urgent to develop wound dressings that integrate antibacterial, anti-inflammatory, wet tissue adhesion, drug loading, biocompatibility, conformability and easy storage.

[0004] Polyacrylic acid (PAA) and its derivatives are low-cost, non-toxic polymers approved by the FDA. They also have dry adhesion and hemostasis capabilities. Many commercial wound dressings have been developed, such as 3MNexcare bandages (Zeng S., Adv. Healthcare Mater. 2022, 11, 2200837). At the same time, polyacrylic acid (PAA) itself has a certain antibacterial effect (Gratzl G. Materials Science and Engineering C, 2014, 38: 94-100). However, PAA-based dressings have poor adhesion under humid conditions and often fall off from the wound due to exudation of blood or other body fluids. A humid environment destroys the hydrogen bonds of the adhesive groups, reduces the surface energy of the substrate, and weakens or even eliminates adhesion (Cui C., Prog. Polym. Sci. 2021, 116, 101388). Therefore, scientists have been committed to developing PAA-based dressings with stronger wet adhesion. Wang et al. developed a PAA derivative prepared from AA and 1-vinylimidazole in ACS Applied Materials Interfaces, 2022, 14 (31): 36166-36177. The dressing can adhere firmly to the wet tissue surface through hydrogen bonding and electrostatic interactions. However, the introduction of 1-vinylimidazole will bring toxic side effects and its biological function is still unclear, so the dressing has not been widely used. In addition to wet tissue adhesion, the anti-inflammatory and drug-loading properties of existing PAA-based wound dressings are also obviously insufficient, which limits the widespread application of this type of dressing. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a polyacrylic acid-based powder wound dressing, so as to solve the defects of the prior art PAA-based dressings in poor adhesion under humid conditions and obviously insufficient anti-inflammatory and drug-loading properties.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing a polyacrylic acid-based powder wound dressing, comprising the following steps: step (1), copolymerizing N-[tris(hydroxymethyl)methyl]acrylamide (THMA) and a solution of acrylic acid (AA) by photopolymerization, and obtaining P(AA-co-THMA) powder by dialysis, pre-freezing, freeze-drying, and grinding;

[0007] Step (2), dissolving P(AA-co-THMA) powder and the drug in deionized water respectively to obtain P(AA-co-THMA) solution and drug solution respectively, mixing the P(AA-co-THMA) solution and drug solution into gel, pre-freezing, freeze-drying and grinding to obtain a polyacrylic acid-based powder dressing.

[0008] The present invention copolymerizes N-[tris(hydroxymethyl)methyl]acrylamide (THMA) and acrylic acid (AA), and utilizes the trihydroxy structure of THMA to shield the repulsive effect between the carboxyl groups of acrylic acid, and can also form hydrogen bonds with the carboxyl groups of acrylic acid. THMA can also form hydrogen bonds, so a more stable gel cross-linking network can be formed. At the same time, the trihydroxyl group of THMA can also form a non-covalent effect with polyhydroxy drugs, thereby improving the drug loading capacity and exerting its good wet tissue adhesion performance.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the photoinitiator used in the photopolymerization is any one or more of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2,4,6-trimethylbenzoyl diphenyl phosphine oxide (TPO), benzophenone (Darocur BP), 2-hydroxy-2-methyl-1-phenylpropanone (Darocur 1173), 1-hydroxycyclohexyl benzophenone (Irgacure 184), and Eosin Y; and the photopolymerization reaction temperature condition is room temperature.

[0011] Furthermore, the mass volume concentration of the photoinitiator is 0.01% to 1%; the wavelength of the light source used in the photopolymerization is 250 to 800 nm, and the irradiation time is 1 to 5 minutes.

[0012] Furthermore, the drug is a polyhydroxy plant extract.

[0013] Furthermore, the plant extract is any one or more of madecassoside, tannic acid (TA), gallic acid, luteolin, and taxifolin; and the drug mass volume concentration is 1% to 10%.

[0014] Furthermore, the mass percentage concentration of N-[tris(hydroxymethyl)methyl]acrylamide in the solution is 9.1% to 20%, and the mass percentage concentration of acrylic acid in the solution is 1.9% to 16.4%; the molar ratio of THMA to AA in the solution of N-[tris(hydroxymethyl)methyl]acrylamide and acrylic acid is 1:5 to 5:1, preferably 1:3 to 3:1.

[0015] Furthermore, the mass percentage concentration of N-[tris(hydroxymethyl)methyl]acrylamide in the solution is 16.7%, and the mass percentage concentration of acrylic acid in the solution is 7.25%; the molar ratio of THMA to AA in the solution of N-[tris(hydroxymethyl)methyl]acrylamide and acrylic acid is 1:1.

[0016] Furthermore, the mass volume concentration of the P(AA-co-THMA) solution is 18 to 37%, and the mass ratio of the P(AA-co-THMA) powder to the drug is 100:1 to 5:1, preferably 50:1 to 10:1, and more preferably 20:1.

[0017] Furthermore, the molecular weight cutoff of the dialysis bag used in the dialysis in step (1) is 8000-14000Mw, the time is 24-120h, and the time interval for replacing deionized water in the dialysis is 8-16h.

[0018] Furthermore, the pre-freezing time in step (1) and step (2) is 12 to 18 hours, and the temperature is -80 to -20°C; the freeze-drying time is 48 to 120 hours, and the temperature is -60 to -20°C; the grinding tool is a mortar or a grinder; the grinding time in step (1) is 10 to 120 seconds; and the grinding time in step (2) is 10 to 30 seconds.

[0019] The present invention prepares a polyacrylic acid-based powder wound dressing in a simple, safe and low-cost manner. All components of the system are safe and reliable and have good biocompatibility; it not only enhances the wet adhesion of the polyacrylic acid-based dressing, but also gives it excellent anti-inflammatory properties.

[0020] The dressing of the present invention is in a dry powder state before application, is easy to store, and can quickly adapt to wounds of irregular shapes, absorb tissue fluid exuded from wounds, and promote wound healing. The powder dressing has potential application prospects in promoting the healing of acute and chronic skin wounds and preventing and treating bone infections. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The powder state photograph and gel state scanning electron microscope (SEM) image of the polyacrylic acid-based powder wound dressing loaded with madecassoside prepared in Example 2 of the present invention are shown in FIG. Figure 1 (a) shows the powder state of the dressing. Figure 1 (b) SEM image showing the gel state.

[0022] Figure 2 The rheological results of the gel sample of the polyacrylic acid-based powder wound dressing loaded with madecassoside prepared in Example 2 of the present invention are as follows: Figure 2 (a) is the storage and loss modulus of P5M1; Figure 2 (b) is P 10 Storage and loss modulus of M1; Figure 2 (c) is P 20 Storage and loss modulus of M1; Figure 2 (d) is the storage and loss modulus of P50M1; Figure 2 (e) is P 100Storage and loss modulus of M1.

[0023] Figure 3 These are the bonding strength results of a series of madecassoside-loaded polyacrylic acid-based powder wound dressings prepared in Example 2 of the present invention on the surface of pig skin.

[0024] Figure 4 The in vitro antibacterial test results of the P(AA-co-THMA) powder prepared in Example 1 of the present invention are as follows: Figure 4 (a) is a photo of bacterial colonies of Staphylococcus aureus and Escherichia coli. Figure 4 (b) Relative bacterial activity of Staphylococcus aureus and Escherichia coli under different treatment conditions.

[0025] Figure 5 This is the fluorescence image result of macrophage polarization induced by the polyacrylic acid-based powder wound dressing loaded with madecassoside prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0026] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0027] Example 1

[0028] Preparation of P(AA-co-THMA) powder: 0.391 mL of acrylic acid (AA) and 1 g of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) were added to 5 mL of deionized water to form a mixed solution, wherein the mass percentage concentration of acrylic acid (AA) was (0.391 / 0.391+5)*100%, i.e. 7.25%, and the mass percentage concentration of THMA was (1 / 1+5)*100%, i.e. 16.7%. 0.0125 g of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) was weighed and added to the mixed solution, stirred continuously until completely dissolved, and then placed in a jar. The mixture was irradiated under ultraviolet light (365 nm) for 1 min for copolymerization to obtain a P(AA-co-THMA) solution, and then the P(AA-co-THMA) solution was placed in a dialysis bag with a molecular weight cutoff of 8000-14000 Mw, dialyzed with deionized water for 72 h, the deionized water was replaced every 12 h, and then placed in a refrigerator at -60°C for 12 h, and then freeze-dried in a vacuum freeze dryer at -55°C for 72 h; dry P(AA-co-THMA) was obtained, and the P(AA-co-THMA) powder with a molar ratio of AA to THMA of 1:1 was obtained by grinding with a grinder for 30 s.

[0029] Examples 1-1 to 1-4 According to Table 1, different masses of AA and THMA were weighed and added into deionized water to form AA and THMA solutions of different concentrations (the mass percentage concentration of N-[tris(hydroxymethyl)methyl]acrylamide solution was 9.1% to 20%, and the mass percentage concentration of acrylic acid solution was 1.9% to 16.4%), and then the steps of Example 1 were followed to obtain P(AA-co-THMA) powders with different THMA contents. The solution name is denoted as A x T y , wherein A represents AA, T represents THMA, and x:y is the molar ratio of AA to THMA.

[0030] Table 1. THMA and AA molar ratio parameters

[0031]

[0032] Example 2

[0033] Preparation of polyacrylic acid-based powder wound dressing: Take 1g of the P(AA-co-THMA) powder obtained in Example 1 and dissolve it in 3mL of deionized water to obtain a P(AA-co-THMA) solution with a mass volume concentration of 25%; Take 0.0375g of madecassoside and dissolve it in 0.75mL of deionized water to obtain a 5% madecassoside solution. Mix all the above solutions and stir them evenly. Then place the mixed solution in a refrigerator at -60°C for 12h, and then place it in a vacuum freeze dryer at -55°C for lyophilization for 72h to obtain a dry polymer, which is ground with a grinder for 30s to obtain a polyacrylic acid-based powder wound dressing with a madecassoside content of 5%.

[0034] In Examples 2-1 to 2-4, different masses of madecassoside were weighed and dissolved in deionized water according to Table 2 to form madecassoside solutions of different concentrations. Then, the steps of Example 2 were followed to obtain polyacrylic acid-based powder wound dressings with different madecassoside contents, denoted as P x M y , wherein P is the P(AA-co-THMA) powder with different THMA contents obtained in Example 1, M is madecassoside, and x:y is the mass ratio of P(AA-co-THMA) powder to madecassoside.

[0035] Table 2. P(AA-co-THMA) powder and madecassoside mass ratio parameters

[0036]

[0037] Test Example 1

[0038] Morphological characterization: The porosity of hydrogel materials plays an important role in the interaction between cells and newly formed tissues. Controlling the porosity and microstructural features in hydrogels can produce engineered tissues that are similar to the structure and function of natural tissues. In addition, by increasing the porosity and improving the 3D structure of the hydrogel, cells can easily pass through and promote the formation of new tissues. Figure 1 The following are the photos of the polyacrylic acid-based powder wound dressing loaded with madecassoside obtained in Example 2 in the powder state (a) and the SEM results after absorbing water to form a gel (b). The results show that the polyacrylic acid-based dressing in the powder state mainly exists in the form of small fragments, and there are no pores in the fragments; after absorbing water to form a hydrogel, an interconnected porous structure is formed inside the dressing. This structure is not only conducive to the absorption of wound exudate, but also helps the exchange of oxygen, water and nutrients, and promotes cell adhesion, migration and extracellular matrix deposition in the wound area.

[0039] Test Example 2

[0040] Rheological properties: The five polyacrylic acid-based powder wound dressings with different madecassoside loadings obtained in Example 2 and Examples 2-1 to 2-4 were added with an equal amount of water to form a hydrogel, and the rheological properties of the hydrogel samples were tested using an AR2000 rheometer from TA Instruments. The fixture was a parallel plate with a diameter of 25 mm, the experimental temperature was 25°C, and the spacing between the parallel plate fixtures was 1 mm. The hydrogel samples were subjected to a dynamic frequency scan, with the strain fixed at 1%, and the frequency scan range being 0.1 to 100 (rad / s).

[0041] The experimental results are as follows Figure 2 As shown, when the scanning frequency is between 0.1 and 100 rad / s, the storage modulus (G') of all samples is always greater than the loss modulus (G") during the entire scanning process, and no intersection occurs between G' and G", indicating that all samples have formed hydrogels. In addition, as the scanning frequency increases from 0.1 rad / s to 100 rad / s, the G' of all samples continues to increase, indicating that the mechanical properties of the formed hydrogels are relatively stable. With the increase of the madecassoside content, the G' and G" of the samples gradually decrease, indicating that the high content of madecassoside reduces the cross-linking degree of the samples to a certain extent. Therefore, in order to ensure sufficient mechanical properties of the hydrogel, the loading amount of madecassoside should not be too large.

[0042] Test Example 3

[0043] Overlap shear performance: Take five kinds of polyacrylic acid-based powder wound dressings with different hydroxy-madecassoside loadings obtained in Example 2 and Examples 2-1 to 2-4, add an equal amount of water to form a hydrogel, and use the HY-1080 universal mechanical testing machine of Shanghai Hengyi Precision Instrument Co., Ltd. to conduct an overlap shear test to test the adhesion performance of the samples on the pig skin surface. The pig skin is made into a size of 25mm×30mm, and the pig skin is tightly adhered to the tinplate sheet with 502 glue. First, add an appropriate amount of water to the pig skin, and then add the powder dressing. Let it stand for 1 hour to form a hydrogel, and then cover it with the other side of the pig skin so that the hydrogel is evenly coated between the two pieces of pig skin. The size of the hydrogel is controlled to be 25mm×20mm×1mm, and the contact area S is 100mm 2 , let it stand for 1 hour, and then perform a uniaxial tensile test at a stretching rate of 0.2 mm / min to obtain the maximum tensile stress F, from which the bonding strength (kPa) of the hydrogel sample on the pig skin is calculated:

[0044]

[0045] The results are as follows Figure 3 As shown, when the loading amount of madecassoside is 5% or less, the dressing loaded with madecassoside (P 100 M1, P 50 M1, P 20 The bonding strength of the dressing M1) is comparable to that of the dressing A1T1 without madecassoside, indicating that the polyacrylic acid-based dressing loaded with madecassoside has good bonding properties. P20M1 The bonding strength is up to 33.3kPa, which is times better than commercial wound dressings. When the madecassoside loading is above 5%, the bonding strength of the dressing shows a downward trend as the madecassoside loading increases. This may be because the high loading of madecassoside reduces the cross-linking density inside the dressing, resulting in a decrease in bonding strength. This result shows the same trend as the rheological results, and the madecassoside loading is preferably 5%.

[0046] Test Example 4

[0047] Evaluation of antibacterial properties: The P(AA-co-THMA) powder of A1T1 obtained in Example 1 was tested for in vitro antibacterial properties, and its antibacterial properties were evaluated using Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli), including the following steps:

[0048] (1) Use a pipette to transfer 100 μL of bacterial suspension to a 96-well plate and use a microplate reader to measure the absorbance (OD) at 600 nm. Use LB to dilute the bacterial suspension to 1×10 7 CFU / mL, continue to dilute the bacterial solution with PBS to 1×105 CFU / mL;

[0049] (2) 1 mg, 2 mg, 4 mg, and 8 mg of A1T1 powder were mixed with 1 mL of 1×10 5 CFU / mL bacterial solution was mixed, with the negative control group without A1T1 powder added, and co-cultured with bacteria at 37°C;

[0050] (3) After 24 hours, the co-culture solution was placed on a vortexer for 1 min to allow the bacteria to fall off and be evenly distributed;

[0051] (4) The shaken bacterial solution was diluted with PBS to 10, 100, and 1000 times in proportion to select a suitable dilution ratio, 100 μL of the diluted bacterial solution was transferred to an agar plate (n=3), glass beads were added and coated using the bead coating method, and the coated agar plate was transferred to a 37°C incubator;

[0052] (5) After 24 hours of incubation, the agar plate was removed and observed and photographed.

[0053] The bacterial colonies were counted by plate counting method, and the relative bacterial activity after adding A1T1 powder was calculated:

[0054]

[0055] Among them, N a Represents the number of bacterial colonies in the control group, N b Representative bacterial colony counts of the experimental groups.

[0056] The results are as follows Figure 5 As shown, for Staphylococcus aureus, only a small number of colonies appeared in the experimental group with an A1T1 powder concentration of 1 mg / mL; and with the increase of dressing concentration, almost no colonies appeared. It was calculated that the bactericidal efficiency of 1 mg / mL AIT1 was 97.75%, 2 mg / mL was 99.78%, 4 mg / mL was 99.89%, and 8 mg / mL was as high as 99.99%. For Escherichia coli, the A1T1 dressing concentration of 1 mg / mL group has shown a strong antibacterial effect, with a bactericidal rate of 88.35%; with the increase of dressing concentration, the antibacterial effect gradually increased; when the dressing concentration was 8 mg / mL, the bactericidal efficiency was 99.99%, indicating that the P(AA-co-THMA) powder has high antibacterial properties.

[0057] Test Example 5

[0058] Evaluation of anti-inflammatory properties: Take the P obtained in Example 2 20 The M1 dressing was tested to induce macrophage polarization, including the following steps:

[0059] (1) Use a pipette to gently blow down the Raw264.7 cells, count them, and dilute them;

[0060] (2) The diluted cell suspension was inoculated into a 24-well plate (1x105 cells / well) and then cultured overnight at 37°C and 5% CO2;

[0061] (3) Dissolve lipopolysaccharide (LPS) in DMEM at a concentration of 1 μg / mL. Aspirate the cell culture medium in the above 24-well plate, add LPS solution, and continue culturing for 6 hours;

[0062] (4) Aspirate the LPS solution and wash twice with PBS. Add a solution containing 8 mg / mL LPS20M1 in DMEM (containing 10% FBS) to the material group, and add a DMEM medium containing 10% FBS to the control group, and continue culturing for 24 hours;

[0063] (5) Aspirate the culture medium and wash twice with PBS. Add 4% paraformaldehyde solution (500 μL / well) and fix at room temperature for 20 minutes;

[0064] (6) Aspirate the paraformaldehyde solution and wash twice with PBS. Add blocking solution (500 μL / well) and block at room temperature for 1.5 hours;

[0065] (7) Aspirate the blocking solution and wash twice with PBS. Add the primary antibody CD163 and incubate at 4°C overnight. Aspirate the primary antibody and wash twice with PBS. Add the corresponding secondary antibody and incubate at room temperature in the dark for 1.5 hours. Aspirate the secondary antibody and wash twice with PBS. Add DAPI to stain the cell nucleus, incubate at room temperature in the dark for 10 minutes, and wash twice with PBS;

[0066] (8) Observe using an inverted fluorescence microscope.

[0067] In this experiment, LPS was first used to induce RAW264.7 macrophages to polarize into M1 type, and then the macrophages were treated differently. Among them, CD163 is a characteristic protein on M2 macrophages, which is shown in red in the picture. Figure 4 As shown, the red fluorescence signal of the control group was very weak; compared with the control group, P 20 The red signal of the M1 group was significantly enhanced, indicating that P20M1 treatment successfully transformed M1 macrophages into M2 macrophages. This result proves that polyacrylic acid-based powder dressings can promote the transformation of macrophages from pro-inflammatory M1 to anti-inflammatory M2.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyacrylic acid-based powder wound dressing, characterized in that: The following steps are involved: Step (1), using photopolymerization to copolymerize N-[tris(hydroxymethyl)methyl]acrylamide and acrylic acid solution, and dialyzing, prefreezing, freeze-drying, and grinding to obtain AA-co-THMA powder; Step (2), dissolving AA-co-THMA powder and the drug in deionized water to obtain AA-co-THMA solution and drug solution respectively, mixing the AA-co-THMA solution and the drug solution into a gel, pre-freezing, freeze-drying, and grinding to obtain a polyacrylic acid-based powder dressing.

2. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 1, characterized in that: The photoinitiator used in the photopolymerization is any one or more of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 2,4,6-trimethylbenzoyl diphenyl phosphine oxide, benzophenone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl benzophenone, and eosin Y.

3. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 2, characterized in that: The mass volume concentration of the photoinitiator is 0.01% to 1%; the wavelength of the light source used in the photopolymerization is 250 to 800 nm, and the irradiation time is 1 to 5 minutes.

4. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 1, characterized in that: The drug in the drug solution is a polyhydroxy plant extract.

5. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 4, characterized in that: The plant extract is any one or more of madecassoside, tannic acid, gallic acid, luteolin and taxifolin; and the mass volume concentration of the drug solution is 1% to 10%.

6. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 1, characterized in that: The mass percentage concentration of the N-[tris(hydroxymethyl)methyl]acrylamide in the solution is 9.1% to 20%, and the mass percentage concentration of the acrylic acid in the solution is 1.9% to 16.4%; the molar ratio of THMA to AA in the N-[tris(hydroxymethyl)methyl]acrylamide and the acrylic acid solution is 1:5 to 5:

1.

7. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 6, characterized in that: The mass percentage concentration of the N-[tris(hydroxymethyl)methyl]acrylamide solution is 16.7%, and the mass percentage concentration of the acrylic acid solution is 7.25%; the molar ratio of THMA to AA in the N-[tris(hydroxymethyl)methyl]acrylamide solution and the acrylic acid solution is 1:

1.

8. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 1, characterized in that: The mass volume concentration of the AA-co-THMA solution is 18 to 37%, and the mass ratio of the AA-co-THMA powder to the drug is 100:1 to 5:

1.

9. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 1, characterized in that: The molecular weight cutoff of the dialysis bag used in the dialysis in step (1) is 8000-14000Mw, the time is 24-120h, and the time interval for replacing deionized water during the dialysis is 8-16h.

10. The method for preparing a polyacrylic acid-based powder wound dressing according to claim 1, characterized in that: The pre-freezing time in step (1) and step (2) is 12 to 18 hours, and the temperature is -80 to -20°C; the freeze-drying time is 48 to 120 hours, and the temperature is -60 to -20°C; the grinding tool is a mortar or a grinder; the grinding time in step (1) is 10 to 120 seconds; the grinding time in step (1) is 10 to 30 seconds.